(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Blood transfusion is always associated with some hazards despite economic and work burden on laboratory staffs. Pre-donation and blood conservation can help to avoid transfusion related hazards with good posto-perative outcome. Objective: The main objective of this study was to show the varieties of cardiac surgery without donor blood transfusion. Methodology: Patients were selected conveniently. Preoperative proper counseling was done to the guardians of minor and all the adult patients about the procedure and written informed consent was taken accordingly. All patients were operated under cardio-pulmonary bypass (CPB) following a standard protocol through mid-sternotomy, systemic heparinization, antegrade intermittent cold cardioplegic arrest of the heart. After weaning from CPB protamine was administered to neutralize the action of heparin. A pre-operative hemoglobin (Hb) and hematocrit (Hct) measured just before systemic heparinization. One bag of blood drawn from the patient’s body when the Hb and Hct more. Meticulous hemostasis done after weaning from cardio-pulmonary bypass. Both systemic and local tranexamic acid plus calcium injection was given before sternal wires are tighten. All the blood in the cardio-pulmonary bypass machine was returned at the end of operation. Patient’s hemoglobin and hematocrit checked to detect the need for transfusion. All other variables were studied. Results: Ten patients were operated without pre-operative blood transfusion of donor blood. Out of ten patients male=5 female=5, Male:Female=1:1 age range 5-26 years mean ±SD (13±-6.88) years. Preop diagnosis ASD 4/10=40%,VSD 3/10=30% TOF 2/10=20% AVR=1/10=10%. pre-operative Hb Range: 12.4-17.3 gm/dl. Mean ±SD (14.25±-1.66 gm/dl. Pre-operative Hct mean±SD (43.7±4.5). Per-operative Hct during CPB Mean±SD (24.9±4). Post-operative Hb mean ±SD (11.25gm±1.18gm). Post-operative Hct mean ±SD (34.3±3.80). Use of cell saver 1/8(12.5%) Post-operative blood loss for ASD,VSD, TOF and AVR were mean ±SD = 140±20.60ml, 156.44±33.84.320.80±60.22ml and 280 ml respectively. Varieties of ionotropes used were: Dopamine Dobutamin Adrenaline. Single ionotrope Dopa/Dobuta5/10=50% Double ionotrope Dopa/dobuta+Adrin=3/10(30%) tripple ionotrope 2/10(20%). Morbidity and mortality 0%. All the patients were discharged home uneventfully, in hospital outcome was good. Conclusion: In our setup we can do cardiac surgery without pre-operative donor blood use by following blood pre-donation and other blood conservative techniques.] Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 53-58